2018
DOI: 10.1002/slct.201801622
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Triazole‐Containing 2‐Phenylindole and Salicylic Acid as Quorum Sensing Inhibitors Against Pseudomonas aeruginosa

Abstract: We designed and synthesized 2‐phenylindole‐amide‐triazole and salicyclic acid‐triazole analogues and characterized using NMR, MS and elemental analysis. Furthermore, single crystal was developed for N‐(2‐Phenyl‐1H‐indol‐3‐yl)‐2‐(4‐propyl‐1H‐1,2,3‐triazol‐1‐yl)acetamide (7 a), 2‐(4‐(4‐(tert‐Butyl)phenyl)‐1H‐1,2,3‐triazol‐1‐yl)‐N‐(2‐phenyl‐1H‐indol‐3‐yl)acetamide (7 h) and 3‐(1‐(4‐Ethylphenyl)‐1H‐1,2,3‐triazol‐4‐yl)‐N‐(2‐phenyl‐1H‐indol‐3‐yl)propanamide (10 j). Final compounds were screened for in vitro quorum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…7), named 4-(1-heptyl-1H-1,2,3triazol-4-yl)-N-(2-phenyl-1H-indol-3-yl)butanamide, was found to have promising quorum sensing inhibitory activity against P. aeruginosa MH602 of 60.82% at 250 μM among the synthesised 2-phenylindoleamide-triazoles. 97 SAR analysis showed that an ethyl group at position four of the aryl portion positively affected the activity, whereas other groups, such as the bromo (-Br) derivative, exhibited moderate activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…7), named 4-(1-heptyl-1H-1,2,3triazol-4-yl)-N-(2-phenyl-1H-indol-3-yl)butanamide, was found to have promising quorum sensing inhibitory activity against P. aeruginosa MH602 of 60.82% at 250 μM among the synthesised 2-phenylindoleamide-triazoles. 97 SAR analysis showed that an ethyl group at position four of the aryl portion positively affected the activity, whereas other groups, such as the bromo (-Br) derivative, exhibited moderate activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The indole-based AHL analogue 9 ( Figure 5 c) and salicylic acid (SA) ( Figure 5 c) can effectively inhibit the P. aeruginosa LasR. Accordingly, in 2018, Sekhar et al designed and synthesized some derivatives of 2-phenylindole-amide-triazole and salicylic acid-triazole; among the compounds, four ( 1 0a – c , 1 1 ) were found to have inhibitory activity ( Figure 5 c) [ 39 ]. Later, the same group developed 1 2a – d ( Figure 5 c) as novel inhibitors of LasR-dependent quorum sensing; these compounds exhibited quorum-sensing inhibitory activity without showing toxic effects on normal cells [ 40 ].…”
Section: Inhibitors Of the Las Systemmentioning
confidence: 99%
“…Studies reported that the indole derivatives 7-fluoroindole, 7-hydroxyindole, and 3-indolylacetonitrile ( Figure 18 a) were potent antivirulence compounds. They reduced the production of QS-regulated virulence factors in P. aeruginosa [ 39 ]. Benzimidazole derivatives 5,6-dimethyl 2-aminobenzimidazole 5 8 and two benzimidazolium salts 59a , 59b ( Figure 18 b) were found to have inhibition effects on the production of QS-regulated virulence factors and biofilm formation in P. aeruginosa [ 140 , 141 ].…”
Section: Inhibition Mechanism Undeterminedmentioning
confidence: 99%
“…In 2018, Srinivasarao et al 110 designed and synthesized 2-phenylindole-amide-triazole and salicyclic acid-triazole analogues (21a–c). These compounds were screened for in vitro quorum sensing inhibitory (QSI) activity against Pseudomonas aeruginosa .…”
Section: Targeting Virulence Factormentioning
confidence: 99%